O maravilhoso reino fungi - Lopes, Euzenir Pinheiro; Dias, Elorita Kátia Malvezzi; Simião, Regina Aparecida Versoza (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf